Canned fish exports: a systematic review of the scientific literature (2001-2021) - Tintaya-Condori, Diana A. (2022)
Objective. To show experiences and export plans of canned fish in South America presented in ScienceDirect, Redalyc, Scielo, Doaj, Econbiz, Sisbib, La Referencia and Fedesarrollo, between the years 2001 and 2021. In addition, the specific objectives were to identify the countries from which these experiences and export plans originate, to which countries they are oriented, their logistic methods, conclusions and recommendations. Method. A systematic review was conducted in which 1,069,944 records were identified, which, after application of exclusion and inclusion criteria, were reduced to 10 final records for analysis. Results. Data was extracted referring to the authors' names, the year of publication, the title of the record, the type of document (thesis, scientific article or technical report), the export product, exporting and importing country, logistic method and conclusions of the original authors. Conclusion. Of the selected records, most of the exports come from Ecuador (4 cases), the most used logistical method is maritime transport and their main destination is the U.S. market (5 cases), which concentrates the greatest demand for canned fish from the region, especially of Ecuadorian origin.